Effect of Betadine Vaginal Preparation during Oocyte Aspiration in in vitro Fertilization Cycles on Pregnancy Outcome - Zreik, Tony (2008)
Objective: The objective of this study is to assess the effect of two methods of vaginal scrubbing before egg retrieval on the outcome of in vitro fertilization-embryo transfer (IVF-ET) cycles. Method: 721 consecutive cycles of IVF-ET, at the American University Hospital of Beirut, were randomized prospectively into one of two groups. In the study group the betadine used to scrub the vagina, prior to egg retrieval, was not washed out, whereas in the control group this betadine was cleansed by saline irrigation. The two groups were compared as to the outcome of their IVF-ET cycles. Result: Both groups were similar in age, mean dose of FSH received, the number of oocytes and embryos obtained, the number of grade 1 embryos obtained, and the fertilization rate. There was no difference in the total pregnancy, clinical pregnancy, missed abortion, and multiple pregnancy rates between the two groups. However, the chemical pregnancy rate was higher in the study group as compared to controls. Conclusion: Vaginal preparation by betadine does not seem to affect the results of IVF. However, because it is associated with an increase in the rate of chemical pregnancy, it is advisable to cleanse before oocyte aspiration.